Population fluctuations in the pink hibiscus mealybug and its natural enemies in Annona squamosa (Annonaceae) in Roraima, Brazil - NEGRINI,Marcelo (2018)
ABSTRACT Maconellicoccus hirsutus (Hemiptera, Pseudococcidae), a species of economic interest, especially for fruit plants, is expanding on the South American continent. Information about the population dynamics of this pest associated with control by natural enemies and cultural practices is fundamental for its management. Our objective was to study the population fluctuations in M. hirsutus and its natural enemies in a sugar-apple (Annona squamosa) orchard in Roraima, northern Brazil. Trees were evaluated monthly over a 12-month period. Infestation rates by M. hirsutus and its parasitism were also estimated for potential host plants around the study area. Highest infestation occurred in August and February-March. Alternative hosts were infested during the off-season, mainly fruit. Lacewings and the parasitoid Anagyrus kamali (Hymenoptera, Encyrtidae) were abundant natural enemies. Average parasitism by A. kamali in fruits was 50%, with highest rates in periods of greatest infestation by M. hirsutus. Fruitification pruning reduced M. hirsutus populations.